Comparison of bleeding and transfusion in patients who undergo coronary artery bypass grafting with and without cardiopulmonary bypass - M Abbaszadeh Ghanavati; F Mehrani; A Boloorian; E Jazayeri Gharehbagh (Tehran University of Medical Sciences, 2011)
Background and Aim: Excessive Bleeding continues to play a key role and an important cause of morbidity and mortality after cardiopulmonary bypass (CPB). The goal of this study was to determine the differences in bleeding and transfusion between OPCAB and on -pump CABG patients. Materials and Methods: In a randomized, double blinded prospective study 300 patient's undergoing coronary revascularization surgery were enrolled, 150 CABG patients were compared with 150 OPCAB patients. The patients were assessed during the first 72 hours to determine the postoperative side effects. The 2 groups were compared using the chi-square test or fisher's exact test and the rank sum test. Results: CABG patients received more intraoperative red blood cells (P<0.0001), more albumin and more fresh- frozen plasma (P<0.0001). Postoperatively, CABG patients were more likely to receive more platelets (29.3% ν 70.7 %, P<0.007). During the operative and the initial 4-hour postoperative period OPCAB patients exhibited greater blood loss (P<0.0001) however, at 12,24and 72 hours postoperatively, CABG patients exhibited greater blood loss. There were4 death in CABG patients (P<0.05) Conclusion: Despite not reversing the heparin at the end of the OPCAB surgery, OPCAB surgery was associated with an overall reduction in platelets, fresh- frozen plasma, Albumin and transfusion requirements.